Digital Transformation of Accounting Information Systems and Organizational Efficiency in Nigeria: An Integrative Review and Research Agenda - Ahmed Hasan; Mohammed Suleiman (PT. BATARI EDU CALYA, 2026)
Digital transformation is reshaping accounting information systems (AIS) from transaction-recording applications into integrated socio-technical infrastructures for real-time reporting, analytics, control, and decision support. This article critically examines how such transformation may influence organizational efficiency in Nigeria. Using a theory-informed integrative review, the study synthesizes peer-reviewed research on digital transformation, AIS, management control, information-system success, and digital public financial management, together with institutional evidence on Nigeria's Treasury Single Account, Government Integrated Financial Management Information System, and Integrated Personnel and Payroll Information System. The synthesis integrates the Technology-Organization-Environment framework, Institutional Theory, and the DeLone-McLean information-systems success model. The evidence indicates that digital AIS can improve transaction speed, information quality, internal control, auditability, decision support, and cross-functional coordination. However, these benefits are contingent rather than automatic. Infrastructure reliability, interoperability, data governance, cybersecurity, managerial commitment, digital competence, process redesign, and institutional enforcement determine whether technological investment is converted into measurable efficiency. Nigeria-specific evidence remains fragmented and is dominated by cross-sectional surveys, conceptual studies, and public-sector reform assessments; consequently, strong causal claims are not yet warranted. The article contributes an integrated mechanism-based framework, identifies boundary conditions particular to developing economies, and proposes a research agenda emphasizing longitudinal designs, objective performance measures, sectoral comparisons, and ethical and cybersecurity risks. For practitioners and policymakers, the central implication is that AIS digitalization should be managed as organizational and institutional transformation, not merely as software acquisition.